Multi-objective optimisation of profile accuracy in two point incremental forming using Taguchi-based grey relation analysis. (2018) - Ragab, Adham E.
This study investigates the effect of four key process parameters in two point incremental forming (TPIF) on the profile accuracy of the manufactured parts. The experiment was applied to A1050-H14 commercial aluminium sheets under different values for tool diameter, feed rate, vertical step size, and sheet thickness. The experiments were designed using the Taguchi L8 orthogonal array. Profile accuracy was estimated by measuring four quality parameters, namely, circularity error, waviness error, depth error, and side wall angle error. Analysis of variance (ANOVA) was used for studying the significance of each process parameter. Grey relational analysis (GRA) was then used to perform a multi-objective optimisation of the four quality parameters simultaneously. The results showed that while each quality parameter may be optimised separately, it is considerably difficult to optimise all of them together. In practice, a compromise must be made based on the profile feature necessary in a given situation.